Calling Ombuds: For Academic Disputes, the Dispute Resolver Must Be Independent from the Institution. Issue 11 (27th November 2022) - Samuel, Adam
Abstract : There are two further issues with university disputes which are connected: the investigation of academic misconduct claims about both students and teachers, and the role of subject‐matter experts.